Groundwater governance in the State of Mato Grosso - Pilar Carolina Villar; Ethiane Agnoletto; Amintas Nazareth Rossete (Derbyana)
Brazilian states have jurisdiction over groundwater and are primarily responsible for its management. Mato Grosso has a state water resources policy and specific regulations for groundwater management, but there is a lack of studies evaluating whether or how this responsibility is being fulfilled. This article aims to assess groundwater governance in the state. To achieve this, besides a document analysis of legislation, scientific literature, and government documents, the methodology developed under the set of indicators of the Groundwater Governance Assessment System (SAGAS) is employed. The institutional and regulatory framework for promoting groundwater governance is shaped by the State Constitution, Law No. 11,088/2020, and Law No. 9,612/2011. Despite this legal and institutional structure, the state struggles to implement the obligations and institutions outlined in its legislation. The state displayed significant weaknesses in all four dimensions: technical (information on aquifers), operational-legal (water resources management tools), institutional-legal (water-focused institutions), and intersectoral political coordination (integration with other policies, such as environmental, sanitation, and agricultural). The score of 91 out of 169 reflects these limitations, which threaten regional water security and resilience. The priority is to consolidate the foundations of the national water resources policy, particularly by establishing all Basin Committees and developing the respective basin plans, as well as implementing water use charges and conducting studies to improve knowledge about the aquifers.